The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Enhancing resilience of maritime transport: theory and practice - Adolf K.Y. Ng; Olivier Faury; Yui-yip Lau; Austin Becker; Ziaul H. Munim (Transportation Research Part D: Transport and Environment, 2025)

Applying MCDA to weight indicators of seaport vulnerability to climate and extreme weather impacts for U.S. North Atlantic ports - R. Duncan McIntosh; Austin Becker (Environment Systems and Decisions, 2020)

Decision makers’ barriers to climate and extreme weather adaptation: a study of North Atlantic high- and medium-use seaports - Elizabeth L. Mclean; Austin Becker (Sustainability Science, 2020)

Institutional and Conceptual Barriers to Climate Change Adaptation for Coastal Cultural Heritage - Alanna Casey; Austin Becker (Coastal Management, 2019)

Fifty Years of Scientific Ocean Drilling - Keir Becker; James Austin; Neville Exon; Susan Humphris; Miriam Kastner; Judith McKenzie; Kenneth Miller; Kiyoshi Suyehiro; Asahiko Taira (Oceanography, 2019)

Climate change impacts on critical international transportation assets of Caribbean Small Island Developing States (SIDS): the case of Jamaica and Saint Lucia - Isavela Ν. Monioudi; Regina Asariotis; Austin Becker; Cassandra Bhat; Danielle Dowding-Gooden; Miguel Esteban; Luc Feyen; Lorenzo Mentaschi; Antigoni Nikolaou; Leonard Nurse; Willard Phillips; David Α.Υ. Smith; et al. (Regional Environmental Change, 2018)

Real-Time Chronological Hazard Impact Modeling - Peter Stempel; Isaac Ginis; David Ullman; Austin Becker; Robert Witkop (Journal of Marine Science and Engineering, 2018)
The potential of using ADvanced CIRCulation model (ADCIRC) to assess the time incremented progression of hazard impacts on individual critical facilities has long been recognized but is not well described. As ADCIRC is applied to create granular impact models, the lack of transparency in the methods is problematic. It becomes difficult to evaluate the entire system in situations where modeling integrates different types of data (e.g., hydrodynamic and existing geospatial point data) and involves multiple disciplines and stakeholders. When considering increased interest in combining hydrodynamic models, existing geospatial information, and advanced visualizations it is necessary to increase transparency and identify the pitfalls that arise out of this integration (e.g., the inadequacy of data to support the resolution of proposed outputs). This paper thus describes an all numerical method to accomplish this integration. It provides an overview of the generation of the hydrodynamic model, describes the all numerical method utilized to model hazard impacts, identifies pitfalls that arise from the integration of existing geospatial data with the hydrodynamic model, and describes an approach to developing a credible basis for determining impacts at a granular scale. The paper concludes by reflecting on the implementation of these methods as part of a Federal Emergency Management Agency (FEMA) Integrated Emergency Management Training Course (IEMC) and identifies the need to further study the effects of integrated models and visualizations on risk perception.

Port Decision Maker Perceptions on the Effectiveness of Climate Adaptation Actions - Adolf K.Y. Ng; Huiying Zhang; Mawuli Afenyo; Austin Becker; Stephen Cahoon; Shu-ling Chen; Miguel Esteban; Claudio Ferrari; Yui-yip Lau; Paul Tae-Woo Lee; Jason Monios; Alessio Tei; et al. (Coastal Management, 2018)

Cost and Materials Required to Retrofit US Seaports in Response to Sea Level Rise: A Thought Exercise for Climate Response - Austin Becker; Ariel Hippe; Elizabeth Mclean (Journal of Marine Science and Engineering, 2017)
Climate changes projected for 2100 and beyond could result in a worldwide race for adaptation resources on a scale never seen before. This paper describes a model for estimating the cost and materials of elevating coastal seaport infrastructure in the United States to prevent damage from sea level rise associated with climate change. This study pilots the use of a generic port model (GenPort) as a basis from which to estimate regional materials and monetary demands, resulting in projections that would be infeasible to calculate on an individual port-by-port basis. We estimate the combined cost of adding two meters of additional fill material to elevate the working surface and then reconstructing the generic port. We use the resulting unit area cost to develop an estimate to elevate and retrofit 100 major United States commercial coastal ports. A total of $57 billion to $78 billion (2012 US dollars) and 704 million cubic meters of fill would be required to elevate the 100 ports by two meters and to reconstruct associated infrastructure. This estimation method and the results serve as a thought exercise to provoke considerations of the cumulative monetary and material demands of widespread adaptations of seaport infrastructure. The model can be adapted for use in multiple infrastructure sectors and coastal managers can use the outlined considerations as a basis for individual port adaptation strategy assessments.

Using boundary objects to stimulate transformational thinking: storm resilience for the Port of Providence, Rhode Island (USA) - Austin Becker (Sustainability Science, 2017)

Stakeholder Perceptions of Seaport Resilience Strategies: A Case Study of Gulfport (Mississippi) and Providence (Rhode Island) - Austin Becker; Margaret R. Caldwell (Coastal Management, 2015)

A note on climate change adaptation for seaports: a challenge for global ports, a challenge for global society - Austin H. Becker; Michele Acciaro; Regina Asariotis; Edgard Cabrera; Laurent Cretegny; Philippe Crist; Miguel Esteban; Andrew Mather; Steve Messner; Susumu Naruse; Adolf K. Y. Ng; Stefan Rahmstorf; et al. (Climatic Change, 2013)

Climate change impacts on international seaports: knowledge, perceptions, and planning efforts among port administrators - Austin Becker; Satoshi Inoue; Martin Fischer; Ben Schwegler (Climatic Change, 2012)

Characterization of full-length MHC class II sequences in Indonesian and Vietnamese cynomolgus macaques - Hannah M. Creager; Ericka A. Becker; Kelly K. Sandman; Julie A. Karl; Simon M. Lank; Benjamin N. Bimber; Roger W. Wiseman; Austin L Hughes; Shelby L. O’Connor; David H. O’Connor (Immunogenetics, 2011)

MHC class I characterization of Indonesian cynomolgus macaques - Chad J. Pendley; Ericka A. Becker; Julie A. Karl; Alex J. Blasky; Roger W. Wiseman; Austin L. Hughes; Shelby L. O’Connor; David H. O’Connor (Immunogenetics, 2008)

Comprehensive characterization of MHC class II haplotypes in Mauritian cynomolgus macaques - Shelby L. O’Connor; Alex J. Blasky; Chad J. Pendley; Ericka A. Becker; Roger W. Wiseman; Julie A. Karl; Austin L. Hughes; David H. O’Connor (Immunogenetics, 2007)